Behaviour of piled raft foundation in sand subjected to combined V-M-H loading. (15th November 2020) - Chanda, Diptesh; Saha, Rajib; Haldar, Sumanta
Abstract: A combined piled raft foundation (CPRF) is generally used for massive and tall structures. The conventional design of piled raft does not include the capacity of piled raft under combined lateral and vertical load. However, vertical ( V ), horizontal ( H ) and moment ( M ) loading may act on the foundation simultaneously. The present study examines the behaviour of piled raft foundation in sandy soil under V-M-H interaction using three-dimensional finite element analysis. The horizontal and moment capacity of piled-raft is assessed due to various influential parameters, such as relative stiffness of pile and soil, raft-soil relative stiffness, spacing to diameter ratio of the pile, length to width ratio of the foundation and pile head connection with the raft. It is observed that piled-raft lateral capacity increases due to combined loading than that of independent capacity. Both failure and design envelopes are also developed considering V-M-H interaction. Finally, the design implication of the outcome of the present study is presented using a case study. It is revealed that the design of piled raft with lateral capacity obtained from the combined action of the V-M-H load may reduce the number of piles as compared to conventional design performed using individual capacity. Highlights: 3D finite element analysis of piled raft foundation embedded in homogenous sandy soil is performed under the application of combined V-M-H loading. The effect of several influential parameters on the lateral response of the piled raft is studied under combined loading. The load sharing between the pile and the raft element in the piled raft under combined loading is presented. Failure, as well as design envelope curves, are proposed for piled raft foundation in the V–H plane. The interaction mechanism of coupled vertical, horizontal, and moment load is studied using a three-dimensional failure envelope in the V-M-H load space.